Concentrated thermionic solar cells using graphene as the collector: theoretical efficiency limit and design rules. (16th November 2021) - Zhang, Xin; Sin Ang, Yee; Ang, Lay Kee; Chen, Jincan
Abstract: We propose an updated design on concentrated thermionic emission solar cells, which demonstrates a high solar-to-electricity energy conversion efficiency larger than 10% under 600 suns, by harnessing the exceptional electrical, thermal, and radiative properties of the graphene as a collector electrode. By constructing an analytical model that explicitly takes into account the non-Richardson behavior of the thermionic emission current from graphene, space charge effect in vacuum gap, and the various irreversible energy losses within the subcomponents, we perform detailed characterizations on the conversion efficiency limit and parametric optimum design of the proposed system. Under 800 suns, a maximum efficiency of 12.8% has been revealed, where current density is 3.87 A cm −2, output voltage is 1.76 V, emitter temperature is 1707 K, and collector temperature is 352 K. Moreover, we systematically compare the peak efficiencies of various configurations combining diamond or graphene, and show that utilizing diamond films as an emitter and graphene as a collector offers the highest conversion efficiency, thus revealing the important role of graphene in achieving high-performance thermionic emission solar cells. This work thus opens up new avenues to advance the efficiency limit of thermionic solar energy conversion and the development of next-generation novel-nanomaterial-based solar energy harvesting technology.